[Laiškas] / Sakovičius (Sakowicz) V. - Adomui Zavadskiui. - (:unkn) unknown (My University, 1853)
1 laiškas apie siunčiamus pinigus už gamtos mokslų istorijos veikalo prenumeratą.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Zawadzki, Adam, 1814-1875; Sakovičius (Sakowicz), V.